OPTIMALISASI KECERDASAN SPIRITUAL ANAK - Rahmat Rifai Lubis (STIT Al-Ittihadiyah Labuhanbatu Utara, 2018)
Everyone has the provision of spiritual intelligence that he brought from birth. In Islam the provision is called Fitrah. Fitrah will grow in accordance with the intake he received, if the received is a positive energy then he grows coloring one's positive side of life, and vice versa. Abdullāh Nāsih 'Ulwān offers some alternatives for the optimization of the spiritual intelligence of the child, including binding the child with worship, binding the child with the Qur'an, binding the child with the house of worship, binding the child to the practice of sunnat, binding the child with the nature of muraqabah to Allah Swt. The existence of spiritual intelligence is at the same pentignya with intellectual intelligence, even its presence to harmonize and optimize the work of intlektual and emotional. Keyword: Optimalisasi, Kecerdasan, Spritual